Chinese medicine formula Kai-Xin-San ameliorates depression-like behaviours in chronic unpredictable mild stressed mice by regulating gut microbiota-inflammation-stress system. (28th October 2020) - Cao, Cheng; Liu, Mengqiu; Qu, Suchen; Huang, Renjie; Qi, Mingzhu; Zhu, Ziqiang; Zheng, Jiani; Chen, Zhichun; Wang, Zhikang; Han, Zhengxiang; Zhu, Yue; Huang, Fei; et al.
Abstract: Ethnopharmacological relevance: Kai-Xin-San (KXS) has been prescribed by TCM doctors for treating psychiatric diseases with the core symptoms of anhedonia, amnesia, and dizziness. According to the symptoms of patients, KXS series formulae are created by varying the compatible ratio of herbs. Today, these formulae are still used in the clinic to treat major depressive disorders. Aim of the study : We hoped to evaluate the antidepressant-like effect of Kai-Xin-San via regulation of the gut-brain axis. Materials and methods: Standardized extracts of three representative compatible ratios of KXS had been prepared, and quality control of the extracts was performed by HPLC-MS/MS. Chronic unpredictable mild stress (CUMS)-induced depression-like mice were used as the depression animal model. After KXS treatment, the antidepressant-like effects of KXS were assessed by behavioural tests. The gut microbiota compositions in the faeces were determined by 16S rRNA sequencing technology. The levels of LPS, pro-inflammatory cytokines and HPA-axis-related hormones were measured by ELISA kits, and the expression of barrier proteins in the small intestines and prefrontal cortex were determined by Western blot analysis. Furthermore, antibiotics were used to determine the correlation between KXS exerting an antidepressant-like effect and regulating the gut-brain axis. Results: KXS alleviated depression-like behaviours in CUMS-exposed mice. Furthermore, these parameters were also found to be changed after KXS treatment. Alteration of the gut microbiota composition were found in the small intestines. A decrease in the LPS and the pro-inflammatory cytokines were found in both the small intestine and brain. An increase in the tight junction proteins was found in the gut epithelium barrier and the blood-brain barrier. A decrease in the stress-related hormones was found in the central nervous system. Furthermore, antibiotic treatment attenuated the antidepressant-like effect of KXS in CUMS-exposed mice. Conclusions: KXS exerted an antidepressant-like effect regulating the gut-brain axis, which included gut micro-environment modification, suppression of neuronal inflammation in the brain and inhibition of HPA axis activation in CUMS-induced depression-like mice. Graphical abstract: Image 1